This Bridge Called Women’s Stories: Private Lore and Public History - Jameson, Elizabeth (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2007)
AbstractThis article traces the achievements and remaining challenges of the project, begun some four decades ago, to integrate women’s experience into “mainstream” history. The author uses her own experience as a women’s historian as well as an analysis of how women have been included in six recent history survey texts (two Canadian, two U.S., two American West). Considerable progress has been made in including women; however, the categories of analysis used in state-centred histories limit the terms of their inclusion. The progress to date also suggests strategies for expanding women’s inclusion, and incorporating gender as a central category of human historical experience.